TINJAUAN KRIMINOLOGI TERHADAP TINDAK PIDANA KORUPSI PENGGELEMBUNGAN ANGGARAN REHABILITASI GEDUNG SMPN 10 METRO YANG DILAKUKAN OLEH APARATUR SIPIL NEGARA (Studi Putusan Nomor : 32/Pid.Sus-Tpk/2021/PN.Tjk) - Bambang Hartono; Zainudin Hasan; Heru Budi Khurniawan (SOL JUSTICIA, 2022)
Crimes of corruption that often occur in the work enviroment service has become a culture that is very difficult to get rid of . Reform it’s been rolling since 1998 which ever since then the screams for democratization and eradication of corruption, nepotism and collusion have resonated great. However, in reality the handling of corruption has arrived at the time this is still not satisfactory. Eradicating corruption is not an easy thing to do. Eradicating corruption is not an easy thing to do. The research problem discusses the factors causing the State Civil Apparatus to commit the criminal act of corruption inflating the rehabilitation budget and a criminological review of the criminal act of corruption inflating the budget based on the Study of Decision Number 32/Pid.Sus-Tpk/2021/Pn Tjk. The research method is normative and empirical juridical, using secondary and primary data, obtained from library research and field studies, and data analysis with qualitative juridical analysis. Based on the results of the research and discussion, the perpetrators of corruption occur because of the destruction of social order as the loss of standards and values. Moral decadence causes corruptors to feel that corruption is common because many have done it. Evil behavior is driven by a weak conscience that is unable to withstand strong urges of lust. The desire to have wealth, wealth and luxury, even if it is obtained from illegal means. It is different from the radical theory, which argues that capitalism is the cause of crime.